2023
DOI: 10.1101/2023.01.03.522213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Gamma-adapted recombinant subunit vaccine induces broadly neutralizing antibodies against SARS-CoV-2 variants and protects mice from infection

Abstract: The COVID-19 pandemic continues with the emergence of successive new variants of concern (VOC). One strategy to prevent breakthrough infections is developing safe and effective broad-spectrum vaccines. Here, we present preclinical studies of a RBD recombinant vaccine candidate derived from the Gamma SARS-CoV-2 variant adjuvanted with alum. Gamma RBD-derived antigen elicited better neutralizing antibody and T cell responses than formulation containing ancestral RBD antigen. The Gamma-adapted subunit vaccine eli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Similarly, booster shots with Beta variant-based vaccines elicit broad nAb responses against the Ancestral, the Beta and the Omicron BA.1 VOC, which were higher in terms of nAb GMT or GMFR than that elicited by the Ancestral prototype vaccines, or a homologous booster with BNT16b2. 10,20,21 Results presented in this work suggest that a booster with ARVAC-CG increases the breath of the nAb and are in agreement with non-clinical results of this vaccine formulation 13 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, booster shots with Beta variant-based vaccines elicit broad nAb responses against the Ancestral, the Beta and the Omicron BA.1 VOC, which were higher in terms of nAb GMT or GMFR than that elicited by the Ancestral prototype vaccines, or a homologous booster with BNT16b2. 10,20,21 Results presented in this work suggest that a booster with ARVAC-CG increases the breath of the nAb and are in agreement with non-clinical results of this vaccine formulation 13 .…”
Section: Discussionsupporting
confidence: 85%
“…Non-clinical studies of this vaccine prototype in mice indicated that the Gamma-variant vaccine-candidate is more immunogenic and induces a broader nAb response than the Ancestral vaccine-candidate. 13 In this interim report safety and immunogenicity data after a booster dose of ARVAC-CG vaccine from an ongoing first in human phase 1 study are presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Moreover, the results from this trial support previous studies indicating increased immunogenicity and breadth of a Gamma-variant vaccine compared to the ancestralvariant vaccine. 13,14 To our knowledge, few trials have simultaneously assessed and compared the immunogenicity outcomes of several vaccine variants, as showed in this Phase III trial, comparing three vaccine versions. 18,19 Bivalent Ancestral/Omicron, Alpha/Beta, and Ancestral/Beta recombinant boosters have previously shown robust nAb responses in individuals who had received primary schemes based mostly on mRNA or Adenoviruses, [18][19][20] but a bivalent recombinant booster vaccine lacking the Ancestral/Alpha variants remained unassessed.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies demonstrated that the Gamma RBD version is more immunogenic than the ancestral RBD at inducing broader neutralizing antibodies (nAbs) even against distant variants, such as the Omicron BA.5. 13 In a Phase I trial, the vaccine was safe and elicited a robust and broad nAb response against several SARS-CoV-2 variants. 14 In this work, we present the results of a Phase II/III trial.…”
Section: Introductionmentioning
confidence: 98%